Amyand hernia; a case report on serendiptous intra-operative diagnosis. (September 2022) - Regmi, Binit Upadhaya; Bhat, Pawan Singh; Bohara, Sujan; Malla, Srijan; Rayamajhi, Jyoti; Karki, Samikshya; Adhikari, Utsab; Rawal, Sushil Bahadur
Abstract: Introduction and Importance: Amyand hernia is an accidental finding that occurs in 0.19–1.7% of patients with inguinal hernia, with children being more commonly affected than adults. However, the management depends on the guidelines given by Losanoff and Basson. Case Presentation: A 62-year-old male presented with complaints of progressive swelling in the right inguinal region without any clinical spectrum of bowel obstruction or strangulation. Examination revealed a right-sided indirect inguinal hernia with positive Ziemann technique. Open hernioplasty revealed an appendix within a hernia sac and was found to be adhered to the surrounding structure with a fibrotic band. According to the Losanoff and Basson protocol, the patient had an appendectomy and an open mesh repair with polypropylene mesh without any post-operative complications. Clinical Discussion: Amyand hernia are often predominantly present in children, with a rare presence in the elderly. Pre-operative clinical diagnosis remains a challenge, and the management depends upon the Losanoff and Basson protocol. Appendectomy of the normal appendix within the hernia sac is often recommended to prevent the sequelae (appendicitis, rupture) following manipulation during hernioplasty. Conclusion: Amyand's hernia is a rare clinical entity and difficult to diagnose due to its uncomplicated presentation. Nevertheless, the progress of appendix inflammation, the possibility of abdominal sepsis, and co-morbidities should all be taken into consideration when deciding how to manage individual patients. Highlights: Amyand's hernia is a rare clinical entity characterized by the presence of a vermiform appendix (normal or inflamed or perforated) within an inguinal hernia sac. Preoperative diagnosis of this clinical condition is uncommon and remains primarily an incidental intra-operative finding. Management with appendectomy is a must to prevent the deleterious sequelae of acute appendicitis and hernioplasty with or without mesh repair depending upon the status of the appendix.